Selective liability, regulated digital commerce, and the subversion of product trading bans: the case of elephant ivory. Issue 3 (4th May 2021) - Cox, Caroline; Collins, Alan
ABSTRACT: This paper outlines and applies the concept of " selective liability" (i.e., operating as if there was a genuine choice between fault-based and strict liability legal regimes) to examine the apparent plausible deniability pact between online selling platforms and the sellers. Through an analysis of online trading data, this paper considered the issues inherent in prosecuting traders who use online auction platforms to sell ivory in contravention of "CITES" regulations. Three bone euphemisms for ivory (antique bovine bone, antique cow bone, antique Chinese cow bone) were identified to track sales over the course of 90 days. The results showed that sellers are using such euphemisms to sell ivory online and these findings highlighted the contradiction between a firm's ban on ivory sales and the apparent ease with which ivory is sold through a website.